KESBAN AT SEA PROJECT : HOLISTIC SECURITY HANDBOOK FOR ESSZONE - Sebastian, Martin A.; Chan, Jennifer Kim Lian (Penerbit Universiti Malaysia Sabah, 2019)
This handbook is an informative guide on the KESBAN at Sea Project. It is a graphic layout of the important elements that are required to achieve Holistic Security for East Sabah. It also entails the need to proceed to Phase II of the project, that is to form the Sabah State ESSZone Committee and proceed with the effort illustrated. MKN Sabah, MIMA and UMS look forward to working together in making East Sabah the El Dorado of the East.